PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN - Princesza Feyga Candi Permana; Antyo Pracoyo (Ibs Press, 2023)
This study aims to determine the influence of work motivation, work discipline and financial compensation on employee performance during the Covid-19 pandemic. The data collection technique uses a questionnaire and uses 30 statement indicators using a Likert scale of 1-6. The sample used in this study were 47 respondents of employees of the DKI Bank Service Office in the south Jakarta Mayor Cluster. Data analysis in this study using Partial Least Square (PLS). Based on the research results, it can be concluded that work motivation has a positive effect on employee performance. Work Discipline has no effect on employee performance. Financial compensation has a positive effect on employee performance.